Pancreatic acinar cell carcinoma with extension into the main pancreatic duct: a case report - Masato Kayahara; Ichiro Onishi; Naoki Makita; Shunsuke Kano; Masayoshi Munemoto; Yasumichi Yagi; Makiko Minami; Noriaki Orita; Takuya Komura; Nozomu Kurose (Surgical Case Reports)
Abstract Background Pancreatic acinar cell carcinoma (PACC) is a rare exocrine malignant tumor. Its widespread intraductal extension into the main pancreatic duct (MPD) is also rare. Case presentation We report the case of a 71-year-old man with PACC with MPD extension. The patient was assessed with laboratory and radiographic investigations that facilitated a preoperative diagnosis. Endoscopic ultrasonography (EUS) and dynamic thin-slice multi-detector row computed tomography (MDCT) were useful for determining the resection line of the pancreas. EUS-guided fine needle aspiration (EUS-FNA) was also helpful in determining the tumor biology and treatment strategy. Distal pancreatectomy was performed. The MPD was occupied by the tumor 35 mm downstream and 5 mm upstream. Histopathologically, the pancreatic tail tumor extended continuously into the MPD. The tumor was solid with cells showing eosinophilic and granular cytoplasm, indicating the diagnosis of PACC. This is an interesting case of PACC with intraductal extension into the MPD. We discuss the possible mechanisms of tumor extension in this rare case together with a review of the literature. Conclusions We describe a rare pancreatic acinar cell carcinoma that could be adequately treated using preoperative precise imaging and histopathological evaluations. When an intraductal tumor extension in the MPD is encountered, the diagnosis of a rare pancreatic tumor should be considered, as in our case.